IDENTIFICATION OF THE STAGES OF STUDENTS’ FIELD-INDEPENDENT CREATIVE THINKING PROCESS IN MATHEMATICS PROBLEM SOLVING - Tampa, Alimuddin; Minggi, Ilham; Alimuddin, Fauziyyah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
The purpose of this study was to describe the creative thinking process of students’ field-independent cognitive style in solving mathematical problems related to the circumference of a flat shape. The method used was descriptive qualitative. The subjects of this study were class VIII students who had a field-independent cognitive style based on the Group Embedded Figure Test (GEFT). Data were obtained through tests, documentation, observation, and interviews. Data analysis was carried out using four creative thinking processes developed by Graham Walla, namely preparation, incubation, illumination, and verification. The results indicated that students could understand the problem well, tend to be quiet to find solutions, could design solutions that would be done by choosing ideas to be solved by modifying the knowledge they already have and applying designed ideas to solve problems. Therefore, students seemed to understand mathematical operations related to the circumference of plat shapes. Abstrak: Tujuan penelitian ini adalah untuk menyajikan proses berpikir kreatif gaya kognitif field-Independent siswa dalam memecahkan masalah matematika berkaitan dengan keliling bangun datar. Metode yang digunakan adalah kualitatif deskriptif. Subjek penelitian ini merupakan siswa kelas VIII yang memiliki gaya kognitif field-independent berdasarkan hasil tes Group Embedded Figure Test (GEFT). Data diperoleh melalui tes, dokumentasi, observasi, dan wawancara. Analysis data dilakukan menggunakan empat proses berpikir kreatif yang dikembangkan Graham Walla, yaitu persiapan, inkubasi, iluminasi, dan verifikasi. Hasil penelitian menunjukkan bahwa Siswa dapat memahami masalah dengan baik, cenderung pendiam untuk mencari solusi, dapat merancang solusi yang akan dilakukan dengan memilih ide untuk diselesaikan dengan memodifikasi pengetahuan yang telah dimiliki, dan menerapkan ide yang dirancang untuk menyelesaikan masalah. Oleh karena itu, siswa tampak memahami operasi matematika yang berkaitan dengan keliling bangun datar.